Improving Studentsâ€™ Critical Thinking Through the Learning Strategy â€œStudents as Researchersâ€: Research Based Learning - Daryanes, Febblina; Ririen, Deci; Fikri, Khusnul; Sayuti, Irda (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking is an intellectual process in making ideas and concepts logically and allows students to analyze their thinking in making choices and drawing appropriate conclusions. However, in fact, in the observations made by lecturers on students, it is still difficult to understand and complete the tasks given by the lecturers, students’ critical thinking skills are still low. This study aims to improve critical thinking skills through the â€œstudent as researchersâ€ strategy. This study uses quantitative analysis with a one group pretest posttest design. The sample in this study were Biology Education students in semester 3 (three) class A who took the Learning Media course. Data were obtained from critical thinking questionnaires and observation sheets. The data were analyzed through significance test and Gain Normalization. The research data shows that students’ critical thinking abilities have increased by 0.70 in the high category after participating in learning with the "Student as Researcher" strategy. The indicator for compiling â€œable to express ideas/ideasâ€ is an indicator that has the highest increase compared to other critical thinking indicators, which is 0.79 in the high category. It can be concluded that the â€œstudent as researchersâ€ strategy can improve students’ critical thinking skills